The liver X receptor agonist LXR 623 restricts flavivirus replication - Mlera, Luwanika; Offerdahl, Danielle K.; Dorward, David W.; Carmody, Aaron; Chiramel, Abhilash I.; Best, Sonja M.; Bloom, Marshall E. (Emerging microbes & infections, 2021)
The vector-borne flaviviruses (VBFVs) are well known for causing great misery and death in humans worldwide. The VBFVs include those transmitted by mosquitos, such as Zika virus (ZIKV), dengue virus; and those transmitted by ticks including the tick-borne flavivirus serocomplex and Powassan virus (POWV). Two of our recent reports showed that intracranial POWV infection in the reservoir host, Peromyscus leucopus, was restricted and caused no overt clinical disease. Several modes of analyses suggested activation of the LXR pathway. Activation of the LXR pathway leads to increased efflux of cholesterol from cells and consequent disturbances in membrane biogenesis. Because VBFV replication is dependent on membrane biogenesis, we evaluated the effect of an LXR agonist (LXR623) on POWV and ZIKV infection and observed that the compound impaired permissive replication of both viruses in a human neuroblastoma SK-N-SH cell line. The LXR agonist resulted in failure of the viruses to induce ER expansion and elaborate vesicle formation, suggesting that the efflux of cholesterol was part of the antiviral mechanism. We also observed that the LXR agonist contributed to the mechanism of virus suppression by increased expression of mRNAs encoding for the antiviral cytokines CXCL10, RANTES and IFN1β. In sharp contrast, a LXR antagonist (GSK2033) had no significant effect on VBFV replication. We conclude that LXR623 impairs flavivirus replication by stimulating cellular antiviral factors.